2019
DOI: 10.1111/febs.14835
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐520c‐3p functions as a novel tumor suppressor in lung adenocarcinoma

Abstract: Lung cancer is a malignancy with one of the highest incidence rates, and it is the leading cause of cancer‐related death. To gain further insights into the underlying mechanisms of tumor growth and metastasis, we investigated the role and expression of microRNAs in lung adenocarcinoma (LUAD). We discovered a significantly lower expression level of microRNA‐520c‐3p (miR‐520c‐3p) in LUAD tissues than in nontumor tissues. miR‐520c‐3p is known to regulate multiple biological functions and cellular behaviors. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Histone methylation also mediates decreased expression of miR-449a via SUZ12 in NSCLC (You et al, 2015). Methylation of the promoter region inhibits the expression of miR-520c-3p, which functions as a novel tumor suppressor in lung adenocarcinoma (Li et al, 2019b). Furthermore, SETDB1 expression can also be regulated by microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Histone methylation also mediates decreased expression of miR-449a via SUZ12 in NSCLC (You et al, 2015). Methylation of the promoter region inhibits the expression of miR-520c-3p, which functions as a novel tumor suppressor in lung adenocarcinoma (Li et al, 2019b). Furthermore, SETDB1 expression can also be regulated by microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the tumor suppressive role of YY1 in lung cancer was also evidenced by the finding that YY1 binds to the promoter of tumor suppressor microRNA-520c-3p and enhances its expression. Enhanced expression of miR-520c-3p inhibits tumor progression by negatively regulating AKT1 and AKT2 (130). Such contrasting roles of YY1 both as a tumor promoter and tumor suppressor is puzzling and further work is required to gain a complete mechanistic insight into these opposing functions of YY1.…”
Section: Lung Cancermentioning
confidence: 99%
“…For example, miRNA-520c-3p is expressed at low levels at the tumour site and negatively regulates the biological behaviour of cancer cells through binding to Akt1 and Akt2. 17 MiRNA-126-3p and miRNA-126-5p are involved in the progression of LUAD and are positively associated with the TNM stage and metastasis. 18 In recent years, accumulating evidence has suggested that competing endogenous RNA (ceRNA) competitively binds to miRNA to regulate miRNA or mRNA expression.…”
Section: Mir-mentioning
confidence: 97%
“…miRNAs control tumour cell stemness and metastasis by acting either as oncogenes or as tumour suppressors. For example, miRNA‐520c‐3p is expressed at low levels at the tumour site and negatively regulates the biological behaviour of cancer cells through binding to Akt1 and Akt2 17 . MiRNA‐126‐3p and miRNA‐126‐5p are involved in the progression of LUAD and are positively associated with the TNM stage and metastasis 18 .…”
Section: Introductionmentioning
confidence: 99%